PENYELENGGARAAN MAKANAN, DAYA TERIMA MAKANAN, DAN TINGKAT ASUPAN SISWA ASRAMA KELAS UNGGULAN SMA 1 PEMALI BANGKA BELITUNG - Sutyawan Sutyawan; Budi Setiawan (Food and Nutrition Society of Indonesia, 2013)
The objectives of this study were to assess food service management, food acceptance, and the consumption’s level of students boarding school dormitory SMA 1 Pemali Bangka Belitung. The research was conducted in May—July 2013 with a cross sectional design. Subjects were purposively chosen with the total of 71 students. As many as 51.0% of components of food service management system have already been applied consisted of planning, purchasing, storage, processing, serving, personal hygiene, and sanitation. Spearman correlation analysis showed that the preference level for taste of food was significantly associated with energy and protein sufficiency level (p<0.05). The preference level for temperature of food was significantly associated with sufficiency levels of phosphorus (p<0.05). Preference level for temperature of food was significantly associated with compliance level of energy and iron (p<0.05). The level of compliance was significantly associated with sufficiency level of energy, iron, phosphorus, and zinc (p<0.05). Energy, protein, fosfor, iron intake from dormitory was significantly negatively associated with intake from non dormitory (p<0.05).